1985
DOI: 10.3109/13682828509012247
|View full text |Cite
|
Sign up to set email alerts
|

Communicative activities of dysphasic adults: a survey

Abstract: This study investigated the communicative activities of 42 dysphasic stroke patients who were living at home. Two aspects of natural communication were surveyed: the conversational communication which occurs with the social contacts of the subject, and the communicative activities of daily living. The two aims of the study were to investigate the relevance of a selection of communicative activities of daily living, and to investigate possible grading of activities so that a representative sample of everyday ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…With regard to aphasia, Holland (1980) has designed a test of functional communication. The search for a method of describing natural communication has been impeded so far because of the wide variation of communicative needs showed by aphasics in real-life situations (Smith, 1985). The objective of this avenue of research is to construct neuropsychological tests with optimal relevance to functional status.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to aphasia, Holland (1980) has designed a test of functional communication. The search for a method of describing natural communication has been impeded so far because of the wide variation of communicative needs showed by aphasics in real-life situations (Smith, 1985). The objective of this avenue of research is to construct neuropsychological tests with optimal relevance to functional status.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have investigated this at different times post onset, for example, Denes et al (1982) followed patients up at six months, Andrews et al (1982) at one year, Kinsella and Ford (1980;1985) at three months and 18 months, at two years, Kotila et al (1986) at four years and Bemspang et al (1987) at four to six years post onset of stroke. Denes et al (1982), as described in section 1.4, completed a study on stroke patients on admission and at six months after onset.…”
Section: Later Post Strokementioning
confidence: 99%
“…They found that all aspects of functional ability were worse in those patients who had drawn abnormal pictures and concluded that cortical dysfunction such as cognitive or perceptual disorders were a major barrier to recovery. Kinsella and Ford (1980;1985), as previously mentioned in section 1.4, followed up 31 stroke patients, aged less than 75 years. They assessed the patients on a cognitive battery of tests, unilateral spatial neglect, motor function and ADL.…”
Section: Later Post Strokementioning
confidence: 99%
See 2 more Smart Citations